2017
DOI: 10.1016/j.jaap.2017.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sawdust addition on coking pressure produced by two low vol bituminous coals

Abstract: Two high-rank bituminous coals and three sawdusts of different origin were selected to study the effect of biomass on coking pressure. The effect of the biomass on the thermoplastic properties of the coals was assessed by means of the Gieseler test. In addition, the effect of the biomass on the thermal decomposition of the coals was studied by means of thermogravimetric analysis together with the modification of the permeability of the coal plastic phase. The individual coals and the blends were carbonized in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…In the case under study, a component that is an inert in the pyrolysis process was introduced which should compensate the effect of increased bulk density. The addition of materials which act as an inert is one of the methods for controlling the coking pressure [61][62][63][64][65]. In the case of biomass, its addition both in loose form and in briquettes resulted in a reduction in coking pressure [34,64].…”
Section: Coke Technological Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case under study, a component that is an inert in the pyrolysis process was introduced which should compensate the effect of increased bulk density. The addition of materials which act as an inert is one of the methods for controlling the coking pressure [61][62][63][64][65]. In the case of biomass, its addition both in loose form and in briquettes resulted in a reduction in coking pressure [34,64].…”
Section: Coke Technological Parametersmentioning
confidence: 99%
“…The addition of materials which act as an inert is one of the methods for controlling the coking pressure [61][62][63][64][65]. In the case of biomass, its addition both in loose form and in briquettes resulted in a reduction in coking pressure [34,64]. Taking into consideration aforementioned information, incorporation of brown coal to the coking blend may reduce coking pressure due not only to the "inert" effect but also due to the "fissure effect".…”
Section: Coke Technological Parametersmentioning
confidence: 99%
“…Moreover coal/biomass blends produce fewer polyaromatic hydrocarbon emissions than coal [8]. The addition of biomass to a coking blend also decreases the coking pressure during the carbonization process [9]. On the other hand, the direct addition of biomass has a deleterious effect on coke quality [9,10] and on the thermoplastic properties of coal [11].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of biomass to a coking blend also decreases the coking pressure during the carbonization process [9]. On the other hand, the direct addition of biomass has a deleterious effect on coke quality [9,10] and on the thermoplastic properties of coal [11]. In recent years however, it has been suggested that the use of briquettes would allow biomass to be added to coking blends without impairing the strength of the resulting bio-coke [12].…”
Section: Introductionmentioning
confidence: 99%
“…7 Non-coking coals and biomasses have been added to coke blends to reduce costs and environmental concerns. [11][12][13] The coking of coal blends has been improved by densifying the coal through stamp charging. 14 Densification has also been shown to improve the coking of coking coal blends, 15 low grade semi-soft coals, 16 non-coking coals, 17 Victorian brown coal 18 and blends of saw-dust and non-coking coal with binder.…”
Section: Introductionmentioning
confidence: 99%